Subjetividade no mundo do trabalho: indivíduo, neoliberalismo e resistência a partir da ressignificação da Bioeconomia - Carvalho, Tainã Alcântara de (2017)
This work starts from the question about the subjectivity in the labor scope under the context of the economic dynamics as bioeconomic, related, thus, to Bioeconomy. The proposal is constituted as a theoretical analysis about the principles of work in the contemporaneity, aiming at the re-signification of the concept of Bioeconomy, initially apprehended from the contributions of Andrea Fumagalli in "Bioeconomy and cognitive capitalism". For that, criticisms, reflections and constitutive propositions are discussed, as well as discussions about the world of work based on the conditions in which the workers are found and the treatments granted to them, especially the possibilities of resistance that they can conjecture in contemporary times through increasingly subtle situations of control and exploitation. In this sense, the present production was developed on a method of bibliographical basis, indicating the need of re-signification of concepts and of exploration and dialogue of contents related to the scope of the world of work. Thus, in correspondence with the contributions of Andrea Fumagalli and the exposition of his theoretical bases, a revision of the concept of Bioeconomy was initially undertaken through a contribution of the Economy through Nicholas Georgescu-Roegen – and his defense of a "minimal bio-economic program" – in order to follow the path through Foucault and his study on biopolitics, Marx and his critique of Political Economy, and in return, Andrea Fumagalli and other contemporary authors, in order to provide the concept of Bioeconomy of substance to analysis, in followed, of the real conditions of insertion of subjectivity in the world of work and of the strategies of resistance employed by individuals through their adaptation to the work context. With this theoretical path, we thus demonstrate proximity to the considerations of the Marxist path of Italian post-operaism, a perspective that will serve as a lens for the best glimpse of the transformations of the world of work. In view of this, the initial considerations point out that the "working individuals" are inserted under a myriad of resistance strategies that follow the forms of control and the processes of productive restructuring in which they are immersed in relation to the labor market, an illustration of the set of employers and companies as a whole. Establishing themselves not as dichotomous, the ideas of resistance or resilience come to be pointed as amalgams of these same positions, with primacy in the contemporaneity of situations of "resilience-resistance" as opposed to "resistance-resilience", a situation in which is sought above all a personal balance within the workplace and a move away from situations that may cause illness. In this section, understandings about Bioeconomy and, at its heart, bioeconomic accumulation, are of importance for the treatment about the ways of controlling human bios within reach of the objectives of capital valorization, from the most basic conception of bios to the physiological aspects of the individual, to the more refined conceptions, related, for example, to the aspects of memory and attention of individuals.